2017
DOI: 10.1055/s-0037-1603462
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Short-Term, and Long-Term Morbidities of Neonates with Birth Weight < 500 g

Abstract: Objectives The objective of this study was to describe survival, short-term, and long-term morbidities of neonates with birth weight < 500 g. Study Design Retrospective cohort studies to calculate survival, short-term, and long-term morbidity rates of neonates born weighing < 500 g from 1993 to 2012 and neurodevelopmental impairment rates at 4.5 years for births 1993 to 2008 in one center. Results Of 549 inborn neonates with birth weight < 500 g, 4% survived. For live births an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…In the literature, normal development is reported in a quarter to one‐third of survivors, 5 , 12 , 15 and survival without severe neurodevelopmental disability ranges from 27 to 71%. 5 , 12 , 13 , 15 , 27 Another factor possibly contributing to developmental delay might be the missing compensatory growth of head circumference until two years corrected age.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, normal development is reported in a quarter to one‐third of survivors, 5 , 12 , 15 and survival without severe neurodevelopmental disability ranges from 27 to 71%. 5 , 12 , 13 , 15 , 27 Another factor possibly contributing to developmental delay might be the missing compensatory growth of head circumference until two years corrected age.…”
Section: Discussionmentioning
confidence: 99%
“…Severe ICH affected 12 of 63 infants (19%), while WMI affected 2 of 62 infants (3%). An ophthalmologic examination was performed in 29 of 71 in- 5 (3)(4)(5)(6)(7)(8)(9)(10) 4 (2-5) 6 (4-10) 46 (4-108) 5 (3-10) 5 (3-10) 4 (2-5) 6 (4-10) 46 (4-108) 5 (3)(4)(5)(6)(7)(8)(9)(10) Abbreviations: GA, gestational age; IQR, interquartile range. a Active treatment was defined as intubation, surfactant therapy, respiratory support, chest compressions, epinephrine, volume resuscitation, blood pressure support, or parenteral nutrition administration.…”
Section: Interventions and Morbidities During Hospitalizationmentioning
confidence: 99%
“…Early analyses reported poor survival for infants born with a BW less than 500 g. 2,3 Reports published since 2010 present improved short-term survival. [4][5][6][7][8][9] In Germany, Rieger-Fackeldey et al 4 found that 60% of liveborn infants with a BW of 500 g or less actively treated at birth survived to discharge. Keir et al 5 reported that 54% of infants with a BW of 500 g or less survived to discharge with active treatment in an Australian center; 43% had no or mild disability at 12 months' corrected age (CA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Donošenje adekvatnih odluka u trenucima reanimacije, zatim donošenje odluka u toku dugog perioda lečenja i neonatalne zdravstvene nege veliki su izazov za zdravstveni tim, i utiču na procenat preživljavanja, morbiditet i neurorazvojne ishode prevremeno rođene dece. 8,9 Različiti koncepti ranih interventnih programa individualno prilagođenih svakom prevremeno rođenom detetu Da bi se poboljšali neurorazvojni ishodi prevremeno rođene dece, osamdesetih godina prošlog veka započeto je razvijanje nekoliko različitih interventnih programa. Jedan od interventnih programa koji je dobio podršku svetski priznatih stručnjaka u oblasti neonatologije i razvojne psihologije bio je "Neonatalna individualizovana razvojna nega i program procene" (engl.…”
Section: Pregledni Rad / Review Articleunclassified